Measuring burnout and work engagement: Factor structure, invariance, and latent mean differences across Greece and the Netherlands - Despoina Xanthopoulou; Arnold B. Bakker; Aristotelis Kantas; Evangelia Demerouti (International Journal of Business Science & Applied Management (IJBSAM), 2012)
This study examines the factor structure and invariance of the instruments measuring burnout (Maslach Burnout Inventory - General Survey / MBI-GS) and work engagement (Utrecht Work Engagement Scale / UWES) in a sample of Dutch (N = 162) and Greek (N = 206) employees. Confirmatory factor analyses in both samples supported the superiority of the proposed three-factor structure of both the MBI-GS (exhaustion, cynicism, and reduced professional efficacy) and the UWES (vigor, dedication, and absorption). Alternative two-factor and one-factor models did not show a better fit to the data. In addition, results of multigroup analyses partly supported the invariance of the three-factor model of the MBI-GS, and fully supported the invariance of the three-factor model of the UWES across the two national samples. These results suggest that the MBI-GS and the UWES are not only valid instruments for testing burnout and engagement but also allow comparisons across countries.
Keywords: 650; burnout; cross-national study; factor structure; invariance; latent mean differences; work engagement